Pushover Analysis of BTN Office Building in Madiun City Indonesia - Kholilur Rohman, Rosyid; ., Rochidajah; Daru Cahyono, Setiyo (International Journal of Engineering and Technology, 2018)
Bank Tabungan Negara office building located in Madiun city, Indonesia. Construction of that building was finished in 2013. BTN office was designed according to SNI 1726 2002. In IndonesiaÂ  there is revision code of SNI 1726 2002 by SNI 1726 2012. Since 2012 planning of building in Indonesia must be designed according to SNI 1726 2012. This research reanalyses this building to know performance level of the building. Pushover analysis use software analysis of structure ETABS version 9.00. Concrete strength used fc 25 MPa, bending reinforcement yield stress fy 400 MPa and shear reinforcement yield stress 240 MPa. Analysis result indicates that performance level of BTN office building is said Life Safety to Collapse Prevention (LS-CP). At the performance point get value of base shear is 1089 KN, and the maximum roof displacement is 127 mm.Â